Status and Perspectives of the Forestry Education in Papua New Guinea - David Lopez Cornelio; Jhon Akande; Efi Yuliati Yovi (Jurnal Manajemen Hutan Tropika, 2011)
The future of forestry within economic and social activities has to be envisioned and defined, in order to better integrate its multi functionality into education. Only a good definition of the roles played by forestry and the responsibilities future practitioners will carry can help define the curricula and methods. A revision of the current status of forestry science development in Papua New G is given considering its geographical location, market new trends, potential advantages, historical enrollments of students and staff, facilities, and nexus with other institutions. It was found that the forestry department of University of Technology Papua New Guinea has been releasing graduates in the last 36 years with a sub optimal formation, the causes are discussed and possible solutions formulated.